2010
DOI: 10.1159/000320379
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic and Prognostic Validity of Golgi Protein 73 in Hepatocellular Carcinoma

Abstract: We regret to inform you that the criticism raised by the Editorial Board is correct concerning the similarity between some parts of the texts present in our article published in Digestion [2011;83:83–88], and the papers in the Journal of Hepatology [2005;43:1007–1012] and in Hepatology [2009;49:1421–1423], although the research data are completely independent. We apologize for this unfortunate error, which was established during the writing process of the manuscript by the author Harun Erdal. Although the fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 42 publications
5
28
2
1
Order By: Relevance
“…This is not in accordance with another study that stated that there was no correlation between GP73 levels and other prognostic parameters including tumor size [24]. This is not in accordance with another study that stated that there was no correlation between GP73 levels and other prognostic parameters including tumor size [24].…”
Section: Figurecontrasting
confidence: 78%
“…This is not in accordance with another study that stated that there was no correlation between GP73 levels and other prognostic parameters including tumor size [24]. This is not in accordance with another study that stated that there was no correlation between GP73 levels and other prognostic parameters including tumor size [24].…”
Section: Figurecontrasting
confidence: 78%
“…The former two are semiquantitative and laborious, but the results of ELISA are disappointing. Six studies [18,21,23,24,27,33] using ELISA method failed to find significant elevation of serum GP73 in HCC groups compared with that in liver cirrhosis groups. Recently described GP73-specific serum autoantibodies might interfere with ELISA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…One of the proteins identified in the serum of woodchucks with cancer and subsequently in the serum of people with HCC was golgi-proteins 73 (GP73). This protein has subsequently been analyzed in over 10,000 individuals with liver disease(Block et al, 2005b; Gu et al, 2009; Hann et al, 2010; Hu et al, 2010; Iftikhar et al, 2004; Jiang and Zhou, 2012; Liu et al, 2011; Maitra and Thuluvath, 2004; Malaguarnera et al, 2010; Mao et al, 2010; Mao et al, 2008; Marrero et al, 2005; Morota et al, 2011a; Ozkan et al, 2011; Riener, 2011; Riener et al, 2009; Schwegler et al, 2005; Shi et al, 2011; Sun et al, 2011; Tan, 2007; Tan et al, 2009; Tian et al, 2011; Wang et al, 2011a; Wang et al, 2009b; Wang et al, 2011b; Xu et al, 2011; Yamamoto et al, 2010; Zhao et al, 2010; Zhou et al, 2012) and for the most part, shown improved performance in the detection of HCC as compared to AFP. However, in several studies, GP73 either was either not elevated in HCC versus cirrhosis (Morota et al, 2011a; Riener et al, 2009) or was no better than AFP at differentiating HCC from cirrhosis.…”
Section: Glycomic Methodologies For the Identification Of Biomarkers mentioning
confidence: 99%